2017
DOI: 10.3390/molecules22111818
|View full text |Cite
|
Sign up to set email alerts
|

How Signaling Molecules Regulate Tumor Microenvironment: Parallels to Wound Repair

Abstract: It is now suggested that the inhibition of biological programs that are associated with the tumor microenvironment may be critical to the diagnostics, prevention and treatment of cancer. On the other hand, a suitable wound microenvironment would accelerate tissue repair and prevent extensive scar formation. In the present review paper, we define key signaling molecules (growth factors, cytokines, chemokines, and galectins) involved in the formation of the tumor microenvironment that decrease overall survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 137 publications
0
37
0
1
Order By: Relevance
“…In tumor microenvironment, cytokines are often characterized as functional redundancy and tissue-specific activities [20,21]. Current studies have shown that over-activated IL-11 contributed to the activation of the gp130 through binding to its receptor in solid tumors [6,11], which afterwards activated JAK/STAT3 pathway that was involved in regulating angiogenesis, metastasis, resistance to apoptosis, cell proliferation, and immune evasion [22].…”
Section: Resultsmentioning
confidence: 99%
“…In tumor microenvironment, cytokines are often characterized as functional redundancy and tissue-specific activities [20,21]. Current studies have shown that over-activated IL-11 contributed to the activation of the gp130 through binding to its receptor in solid tumors [6,11], which afterwards activated JAK/STAT3 pathway that was involved in regulating angiogenesis, metastasis, resistance to apoptosis, cell proliferation, and immune evasion [22].…”
Section: Resultsmentioning
confidence: 99%
“…Soluble mediators, mainly growth factors, cytokines and chemokines, in addition to host immune cells are also produced by cancer-associated fibroblasts (CAFs) or by tumour cells themselves. Several growth factors, namely TGF-β, insulin-like growth factor 2 (IGF-2) and vascular endothelial growth factor (VEGF), cytokines, namely IL-1, IL-4, IL-6, IL-8, IL-10 and tumournecrosis factor alpha, chemokines, namely chemokine (C-X-C motif) ligand 1 and C-C motif chemokine receptor 7, have been reported to be closely involved in tumour progression, invasion and immune escape (Eftekhari et al 2017, Gál et al 2017, Setrerrahmane & Xu 2017 and are potential targets for anti-tumour therapies. Moreover, cancer cells not only express these soluble mediators but also frequently overexpress the related receptors to escape from the immune responses (Setrerrahmane & Xu 2017).…”
Section: Mechanisms Of Immune Suppression or Immune Escapementioning
confidence: 99%
“…Bead-based and planar antibody arrays have been utilized or are potentially applicable to a wide range of cancer studies, including search for diagnostic and prognostic biomarkers, evaluation of antitumour treatment efficacy, understanding of the biology underlining tumourigenesis and tumour progression [ 123 , 135 , 136 ], including mapping the role of tumour microenvironment and inter-cellular cross-talk [ 137 ].…”
Section: Cytokine Detection Techniquesmentioning
confidence: 99%